1993
DOI: 10.1111/j.1432-1033.1993.tb18360.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the brain‐specific expression of the rat aldolase C gene: ex vivo and in vivo analysis

Abstract: A 115‐bp promoter fragment of the aldolase C gene is sufficient for conferring neural cell specificity on a reporter gene, in cultured PC12 cells and in transgenic mice. In vitro DNase I protection experiments detected two footprints on the promoter, termed boxes A/A', and B. The 5′ A/A' box contains overlapping Sp1 and Krox20/Krox24 binding sites; it binds Sp1 in fibroblasts (box A') and a different complex in brain (box A). Any deletion or mutation of this box that impairs protein recognition also suppresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 38 publications
(40 reference statements)
4
24
0
Order By: Relevance
“…CAT activities directed by the TABLE I CAT activity of aldolase C/CAT transgenes in brains of transgenic mice For each transgenic mouse, three other tissues were tested (heart, lung, and liver); CAT activities were at least 100 -1000-fold lower than in brain. 0.8/CAT transgene were in the same range as those obtained with the 0.115/CAT transgene containing the short promoter alone (10,11).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…CAT activities directed by the TABLE I CAT activity of aldolase C/CAT transgenes in brains of transgenic mice For each transgenic mouse, three other tissues were tested (heart, lung, and liver); CAT activities were at least 100 -1000-fold lower than in brain. 0.8/CAT transgene were in the same range as those obtained with the 0.115/CAT transgene containing the short promoter alone (10,11).…”
Section: Resultssupporting
confidence: 67%
“…In Vivo, an Upstream 0.6-kb Fragment and a Far Upstream 3.8-kb Fragment Are Both Necessary for High Level Expression of the Aldolase C Transgenes-Using the CAT reporter gene, we previously showed that the transcriptional activity of the rat aldolase C gene in transgenic mice was ensured by a short 115-bp promoter that was brain-specific, but that was considerably more active when present in a construct containing 5.5 kb of aldolase C upstream sequences (10,11). To localize activating sequences in this 5.5-kb fragment, we analyzed, in transgenic mice, various combinations of aldolase C gene 5Ј-noncoding sequences fused to the CAT reporter gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gel shift experiments confirmed that this region in RI␤ binds pure SP1 and additional proteins in brain nuclear extract (21). Similar sequences are present in a number of genes expressed in neural tissue (37,38), including the promoter for the RII␤ subunit of PKA (39), and are required for expression of aldolase C in mouse brain (40). Sequences such as these have also been shown to bind inhibitors of transcription (41).…”
Section: Discussionmentioning
confidence: 95%